Theoretical Modelling of Aeroheating on Sharpened Noses Under Rarefied Gas Effects and Nonequilibrium Real Gas Effects - Wang, Zhi-Hui.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
Theoretical Modelling of Aeroheating on Sharpened Noses under Rarefied Gas Effects and Nonequilibrium Real Gas Effects employs a theoretical modeling method to study hypersonic flows and aeroheating on sharpened noses under rarefied gas effects and nonequilibrium real gas effects that are beyond the scope of traditional fluid mechanics. It reveals the nonlinear and nonequilibrium features, discusses the corresponding flow and heat transfer mechanisms, and ultimately establishes an analytical engineering theory framework for hypersonic rarefied and chemical nonequilibrium flows. The original analytical findings presented are not only of great academic significance, but also hold considerable potential for applications in engineering practice. The study explores a viable new approach, beyond the heavily relied-upon numerical methods and empirical formulas, to the present research field, which could be regarded as a successful implementation of the idea and methodology of the engineering sciences.
Introduction -- Theoretical Modeling of Aeroheating under Rarefied Gas Effects -- Theoretical modeling of the chemical nonequilibrium flow behind a normal shock wave -- Theoretical modeling of aero-heating under nonequilibrium real gas effects -- Conclusions and prospect.
Keywords: Fluid mechanics; Fluids; Aerospace engineering; Astronautics; Engineering Fluid Dynamics; Fluid- and Aerodynamics; Aerospace Technology and Astronautics